My Hollywood : A Novel - Simpson, Mona (London Corsair, 2012)
Struggling with her television writer husband's long hours and her own lack of childcare experience, composer and new mother Claire hires Lola, a Filipino mother of five seeking to finance her children's education back in the Philippines, who becomes privately devoted to her employers
Keywords: Motherhood -- Nannies -- California--Los Angeles--Hollywood